Analisis Pesan Dakwah Koh Dennis Lim Tentang Judi di Media Sosial Instagram - Sabila Nur Aryani; Afidah, Ida; N. Sausan M. Sholeh (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. This research is entitled "Analysis of Koh Dennis Lim's Da'wah Message on Gambling on Instagram Social Media". This research delves deeper into the analysis of Koh Dennis Lim's content about Gambling on his Instagram. The method used is Content Analysis, a qualitative data collection method. This research focused on the reasons Koh Dennis Lim mentioned about gambling on his Instagram, how Koh Dennis Lim preached on his Instagram, and the content of Koh Dennis Lim's messages about gambling on his Instagram. In this study there are three da'wah messages about gambling that focus more on how to quit gambling addiction. The results of this study are divided into three aspects, namely a descriptive analysis approach that explains in detail how to quit gambling addiction, an explanatory analysis approach that explains how to preach Koh Dennis from the aspects of video editing, captions, and voice intonation, and a predictive analysis approach reviewed from the Youtube podcast visited by Koh Dennis Lim discussing gambling. Abstrak. Penelitian ini berjudul tentang “Analisis Pesan Dakwah Koh Dennis Lim tentang Judi di Media Sosial Instagram“. Penelitian ini menggali lebih dalam analisis konten Koh Dennis Lim tentang Judi di Instagram miliknya. Metode yang digunakan adalah Analisis Konten metode pengumpulan data yang bersifat kualitatif. Penelitian ini difokuskan kepada alasan Koh Dennis Lim menyinggung tentang judi di Instagram miliknya, cara berdakwah Koh Dennis Lim di Instagram miliknya, dan isi pesan Koh Dennis Lim tentang judi di Instagram miliknya. Dalam penelitian ini terdapat tiga pesan dakwah tentang judi yang lebih memfokuskan cara berhenti dari kecanduan judi. Hasil penelitian ini dibagi menjadi tiga aspek yaitu pendekatan analisis deskriptif yang menjelaskan secara rinci cara berhenti dari kecanduan judi, pendekatan analisis ekplanatif yang menjelaskan cara berdakwah Koh Dennis dari aspek video editing, caption, dan intonasi suara, dan pendekatan analisis prediktif yang ditinjau dari podcast Youtube yang didatangi Koh Dennis Lim membahas tentang judi.